2023
DOI: 10.1021/acs.joc.3c01225
|View full text |Cite
|
Sign up to set email alerts
|

Can Catenated Nitrogen Compounds with Amine-like Structures Become Candidates for High-Energy-Density Compounds?

Xinbo Yang,
Nan Li,
Yuchuan Li
et al.

Abstract: The worthwhile idea of whether amine-like catenated nitrogen compounds are stable enough to be used as high-energy materials was proposed and answered. Abstracting the NH 3 structure into NR 3 (R is the substituent) yields a new class of amine-like catenated nitrogen compounds. Most of the azole ring structures have a high nitrogen content and stability. Inspired by this idea, a series of new amine-like catenated nitrogen compounds (A1 to H5) were designed, and their basic energetic properties were calculated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…This conclusion that longer catenated nitrogen structures have a higher enthalpy of formation is consistent with the conclusion obtained from our previous study of amine-like catenated nitrogen structures. 44 Overall, the shapes of the curve ( A x , B x , C x , D x , E x , F x , x = 2 to 6 ) are basically the same, indicating that the influence of different connection modes on the enthalpy of formation are basically the same in both of azobis-1,2,3-triazole and azobis-1,2,4-triazole. In addition, by comparing the enthalpy of formation of azobistriazole derivatives containing oxidizing moieties, it can be found that the order of effect of different oxidizing energetic functional groups on the enthalpy of formation of materials is: C(NO 2 ) 3 > NHNO 2 > NO 2 > NF 2 > ONO 2 .…”
Section: Resultsmentioning
confidence: 81%
“…This conclusion that longer catenated nitrogen structures have a higher enthalpy of formation is consistent with the conclusion obtained from our previous study of amine-like catenated nitrogen structures. 44 Overall, the shapes of the curve ( A x , B x , C x , D x , E x , F x , x = 2 to 6 ) are basically the same, indicating that the influence of different connection modes on the enthalpy of formation are basically the same in both of azobis-1,2,3-triazole and azobis-1,2,4-triazole. In addition, by comparing the enthalpy of formation of azobistriazole derivatives containing oxidizing moieties, it can be found that the order of effect of different oxidizing energetic functional groups on the enthalpy of formation of materials is: C(NO 2 ) 3 > NHNO 2 > NO 2 > NF 2 > ONO 2 .…”
Section: Resultsmentioning
confidence: 81%